Education and democracy: the experience of a participatory action research with upper secondary education teachers in a Piemonte area - Boeris, Cristina (Form@re - Open Journal per la formazione in rete, 2018)
This paper aims to present some of the intermediate results of a PhD research on “Teaching Citizenship and the Italian Constitution in a Community of Democratic Practice” which is taking place at the University of Tourin (Department of Educational Sciences). The research has been structured as a research-training, that is a way for the in-service teachers’ training, according to the Decree n. 797/2016. It has been carried out with three groups of upper secondary education teachers in a Piemonte area. It has produced a useful scheme for programming for citizenship skills, a reflection on the importance of the relational climate among teachers and on the features of the school environment that are required to be a Community of democratic Practice. Educazione e democrazia: l’esperienza di una ricerca-formazione con docenti di scuola secondaria di secondo grado in Piemonte Il contributo intende presentare alcuni risultati della ricerca di dottorato dal titolo “L’insegnamento di Cittadinanza e Costituzione in una comunità di pratica democratica”, al momento in corso presso il Dipartimento di Scienze dell’Educazione dell’Università degli Studi di Torino. La ricerca si è strutturata come una ricerca-formazione, costituendo una modalità per la formazione continua dei docenti in servizio secondo le indicazioni del D. M. 797/2016. Essa si è svolta con tre gruppi di docenti delle scuole secondarie di secondo grado del Piemonte e ha prodotto uno schema utile per la programmazione per competenze di cittadinanza, una riflessione sull’importanza del clima relazionale tra i docenti e su quali caratteristiche deve avere l’ambiente scolastico per essere Comunità di Pratica democratica.